Multi-Omics Characterization of Circular RNA-Encoded Novel Proteins Associated With Bladder Outlet Obstruction - Zhu, Baoyi; Kang, Zhanfang; Zhu, Sihua; Zhang, Yuying; Lai, Xiangmao; Zhou, Lilin; Huang, Hai; Gao, Xiaofeng; Jiang, Chonghe; Zeng, Jianwen (Frontiers in Cell and Developmental Biology, 2022)
Bladder outlet obstruction (BOO) is a common urologic disease associated with poorly understood molecular mechanisms. This study aimed to investigate the possible involvements of circRNAs (circular RNAs) and circRNA-encoded proteins in BOO development. The rat BOO model was established by the partial bladder outlet obstruction surgery. Differential expression of circRNA and protein profiles were characterized by deep RNA sequencing and iTRAQ quantitative proteomics respectively. Novel proteins encoded by circRNAs were predicted through ORF (open reading frame) selection using the GETORF software and verified by the mass spectrometry in proteomics, combined with the validation of their expressional alterations by quantitative RT-PCR. Totally 3051 circRNAs were differentially expressed in bladder tissues of rat BOO model with widespread genomic distributions, including 1414 up-regulated and 1637 down-regulated circRNAs. Our following quantitative proteomics revealed significant changes of 85 proteins in rat BOO model, which were enriched in multiple biological processes and signaling pathways such as the PPAR and Wnt pathways. Among them, 21 differentially expressed proteins were predicted to be encoded by circRNAs and showed consistent circRNA and protein levels in rat BOO model. The expression of five protein-encoding circRNA were further validated by quantitative RT-PCR and mass spectrometry. The circRNA and protein profiles were substantially altered in rat BOO model, with great expressional changes of circRNA-encoded novel proteins.